Safety Management of Environmental Protection and Preservation and Sustainable Development of the Local Community - Nikitović, Zorana; Djuričić, Milan; Djuričić, Milutin (<center>Conference Proceedings Determinants Of Regional Development</center>, 2021)
Many security risks lurk in the modern world, including security risks in the field of environmental protection and preservation. Ensuring the quality of the environment means maintaining the local and planetary biosphere as an essential support system for the realization of all human activities, and above all, the concept of sustainable development of the local community. Therefore, a systematic approach to safety management in the field of environmental protection and preservation must be provided. As a result, an adequate local community security strategy should be developed at the local level.